The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1016/s0022-5223(98)70136-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of myocardial mitochondrial function after hemodynamic support with left ventricular assist devices in patients with heart failure

Abstract: Cardiomyocyte mitochondrial function is improved by long-term therapy with a left ventricular assist device. This improvement suggests that cardiomyocyte metabolic dysfunction in heart failure may be reversed with left ventricular assist device support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 22 publications
4
53
0
1
Order By: Relevance
“…58 Most of these result in depletion of myocardial ATP, phosphocreatine, and creatine kinase, with decreased efficiency of mechanical work. 58 Generally, improvement in cardiomyocyte metabolic dysfunction occurs after LVAD unloading, 59 although the mechanisms involved are still unclear.…”
Section: Metabolic Enzymesmentioning
confidence: 99%
“…58 Most of these result in depletion of myocardial ATP, phosphocreatine, and creatine kinase, with decreased efficiency of mechanical work. 58 Generally, improvement in cardiomyocyte metabolic dysfunction occurs after LVAD unloading, 59 although the mechanisms involved are still unclear.…”
Section: Metabolic Enzymesmentioning
confidence: 99%
“…In end-stage heart failure (HF) patients undergoing transplantation, the rate of respiration in fibers per mg protein (Sharov et al 2000) or in isolated mitochondria per mg mitochondrial protein (Lee et al 1998) was similar in both ventricles. In fibers from atrial appendages, the respiration rate with all substrates is lower compared to ventricles, showing the decrease in mitochondrial content, but when OXPHOS was corrected for the amount of mitochondria (using the maximum uncoupled respiration) the respiration was similar in the three chambers .…”
Section: Anatomical Sites In the Heartmentioning
confidence: 99%
“…A few studies have shown that some treatments for severe HF improved mitochondrial function and structure, e.g., longterm implantation of left ventricular assist devices improved OXPHOS capacity (Lee et al 1998), beta-blocker therapy reversed part of the defect in ETC activity (Scheubel et al 2002), and administering a beta-adrenoceptor agonist increases cristae-to-matrix ratio and mitochondrial size (Unverferth et al 1980). An evolving trend in the treatment of cardiac disease is the use of metabolic modulators, including therapeutic targets aimed at improving mitochondrial energy production (reviewed by Murray et al 2007) to prevent or reverse the low energy status of the failing heart.…”
Section: Mitochondrial Function In the Prevention And Treatment Cardimentioning
confidence: 99%
“…9 It has been suggested that mechanical unloading provides enough improvement to make cardiac transplantation unnecessary in some patients, 10 although others have disagreed with this contention. 11 Recent studies comparing tissue removed at LVAD implantation to the heart at transplantation have suggested that LVAD support improves the structure and function of cardiac myocytes, leading to decreased cell size, 12,13 increased contractility of cells 13,14 and muscles, 15 improved function of intracellular organelles, 15,16 and altered gene expression. 15,17,18 An important compensatory mechanism for maintaining adequate tissue perfusion during functional impairment of the heart is augmentation of cardiac output by the sympathetic nervous system.…”
mentioning
confidence: 99%